Upaya Kepala Sekolah dalam Meningkatkan Eksistensi Sekolah - Muhamad Arifin (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The importance of education in schools in order to realize its goals, namely learning activities, so that all school organizational activities lead to the achievement of efficiency and effectiveness of learning. Teachers play a role not only as agents of change that drive the wheels of social and economic transformation in society. It not only changes students' lives, but also enriches and strengthens students' personalities to become human beings with virtues because they have values that they want to strive for and realize in society. The principal as a leader in every educational institution must be able to think about the relationship between education and the development and development of science and technology which is always changing so that there is a need for work motivation or work motivation.